Epidemiology of symptoms of dry eye disease (DED) in Jordan: A cross-sectional non-clinical population-based study. - Bakkar, May M.; Shihadeh, Wisam A.; Haddad, Mera F.; Khader, Yousef S. (Contact Lens & Anterior Eye, 2016)
Purpose: To describe the prevalence of dry eye disease (DED) symptoms and to identify associated risk factors in a general non-clinical population in Jordan.Methods: In this cross-sectional study, participants were selected randomly from the general non-clinical population in Jordan. Participants aged 18 years or over completed the Arabic version of Ocular Surface Disease Index (OSDI) questionnaire on dry eye symptoms.Results: The OSDI questionnaire was completed by 1039 subjects (609 female and 430 male). The mean OSDI score for the study population was 27, with 59% of subjects showed OSDI score ≥20 (a cut off score for mild DED symptoms). Females showed significantly higher mean OSDI score than males in the older age group (p=0.01). The prevalence of all dryness symptoms was markedly reported in older age group >45 years and contact lens wearers (p<0.05). The most commonly reported DED symptom was sensitivity to light and intense symptoms were markedly reported during windy conditions. Vision-related quality of life was also affected in subjects with dryness symptoms. Working with computers and ATM was among those that highly affected.Conclusion: The results show that symptoms of dry eye were prevalent in this non-clinical population. Contact lenses wear and older age were found to be associated with dry eye symptoms.